Sentinel lymph node detection in early uterine cervical cáncer - Valdivia, Henry (2014)
Objectives: To determine sentinel node (SN) detection feasibility and safety by using lymphatic mapping with 99m Tc dextran and injection of blue dye (patent blue) in patients with early cervical cáncer undergoing radical hysterectomy with bilateral pelvic lymphadenectomy. Design: Prospective study. Setting: Instituto Nacional de Enfermedades Neoplasicas, Lima, Peru. Participants: Patients with early cervical cancer. Interventions: Between December 2003 and December 2006, 66 patients with early cervical cancer stages IA2 (n = 2), IB1 (n = 63) and IIA (n = 1) underwent sentinel lymph node detection with lymphoscintigraphy the day before operation and intraoperative lymphatic mapping with blue dye and gamma radiation detection probe. Surgical treatment was completed with radical hysterectomy and bilateral pelvic lymphadenectomy by laparotomy. Main outcome measures: Sentinel node detection. Results: One hundred and thirty-six sentinel nodes were detected in all 66 patients, average 2.06 per patient, by using the combined method 99m Tc dextran and patent blue. Most common location was the obturator region in 69.9% of cases (n = 95). Pelvic lymph node metastases were found by the sentinel node in 11 patients (sensitivity of 100%). In negative sentinel node cases (55 patients) no metastases were encountered (negative predictive value, NPV =100%). Conclusions: Sentinel node identification using 99m technetium dextran and blue dye injection is feasible and had  a negative predictive value of 100%.